Biological Shielding Design of In Vitro Test Facility Boron Neutron Capture Therapy (BNCT) at Radial Piercing Beam Port of Kartini Research Reactor Using MCNPX - Widarto Widarto; Buyung Edi Prabowo (Indonesian Journal of Physics and Nuclear Applications, 2016)
This research aimed to determine material specification of radiation biological shielding design of neutron and gamma output on radial piercing beamport of Kartini Research Reactor using MCNPX code,  as safety radiation protection purpose of in vitro / in vivo irradiation test facility. Refference input data using parameters of neutron and gamma as result simmulation researcher before  as follows Фth is 5.00 x 108 n.cm-2s-1, Фepi is 1.23 x 108 n.cm-2s-1, Фfast is 1.35 x 109 n.cm-2s-1, Ḋγ is 2.49 x 10-3 Sv.s-1, Ḋn is 3.63 x 10-1 Sv.s-1. [ Dwi W.]Optimation result of simulation using MCNPX to determine specification material for radiation protection safety are parafin block with thickness  75 cm for neutron shielding  and covered by material lead (Pb) with thickness 15 cm for gamma shieding. By this optimation for the both thickness materials, determination for neutron and gamma dose rate  are as follow , Ḋn = 1,1 x Sv.s-1 and with Ḋγ = 1,1 x 10-09 Sv.s-1. Those radiation dose rate of neutron and gamma parameters are still under requirement  of safety dose standard that is 2.78 x 10-9 Sv.s-1 as regulation of Regulatory Body BAPETEN. [Perka BAPETEN No. 4 Tahun 2014]. It can be concluded that by the Biological Shielding Design of In Vitro Test Facility Boron Neutron Capture Therapy (BNCT) at Radial Piercing Beam Port of Kartini Research Reactor Using MCNPX can operated safely.